Manejo nitrogenado e fitossanitário no patossistema soja - Phakopsora pachyrhizi - Maffini, Francis Sartori (2014)
This study aimed to evaluate the performace of soybean cultivar subjected to nitrogen and plant management , depending on the supply of nitrogen and fungicide protection programs for disease. To this end an experiment was conducted in the floodplain environment and another in coxilha environment, in the municipality of Sao Sepe - RS , using a randomized block design with split-split plots with a factor in range . The first factor ( cultivars ) was arranged in the main plots on track . The second factor (nitrogen ) was willing subplots and the third factor ( fungicides ) was randomized within subsubplots . Four replications ( blocks ) were used . Soybean cultivars RR Turbo BMX , were used , NA 5909 RG and BMX Potencia RR. As a second factor , seasons of nitrogen supply , was composed of four levels : N1 - inoculation with Bradyrhizobium japonicum ; N2 - inoculation with B. japonicum + N coverage ; N3 - inoculation with B. japonicum sowing + N , N 4 - inoculation with B. japonicum + N + N seeding coverage. And as a third factor protection programs sprayed the phenological stages V6 and only strobilurin , R1 , R3 and R5 triazole mixture strobilurin disease , They are: T1 - control without fungicide application , T2 - >> Azoxystrobin Azoxystrobin + Cyproconazole; T3 - Piraclostobina >> Pyraclostrobin + Epoxiconazole , T4 - Trifloxystrobin >> Trifloxystrobin + Prothioconazole. We evaluated the relative chlorophyll content ( TRC ) in the three thirds of the canopy , plant height , dry shoot mass , defoliation ( % ) , severity and area under disease progress curve ( AACDP ) , grain yield and thousand grain weight . The rust control using different protection programs for disease varied according to cultivar . The lowest values of defoliation and AACPD were observed with the nitrogen supply , as the application of fungicides provided lower values . Higher productivity differences relative to nitrogen was observed in the floodplain environment where the supply of seed and coating gave the highest yield .